"As jou broer verkeerd opgetree het teen jou...": Enkele aspekte van kerklike dissipline uit die Kerkorde van die Nederduitsch Hervormde Kerk van Afrika - Wyk, Barry van (HTS teologiese studies, 2008)
“If a brother sins against you ...”: Certain aspects of church discipline from the Church Ordinance of the Netherdutch Reformed Church of AfricaChurch discipline has been a substantial part of Church Ordinances since the Geneva Church Ordinance of 1541, and was pursued and developed in the Netherlands and consequently also in South Africa. For obvious reasons church discipline forms part of the Church Ordinance of the Netherdutch Reformed Church of Africa. An effort is made to partly rewrite the church discipline and also to alter and to make the existing appeal possibilities more accessible, particularly with regard to the verdicts of the Synodical Commission.